Pengaruh Return on Asset, Earning Per Share, dan Debt to Equity Ratio Terhadap Harga Saham di Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia pada Periode 2019-2023 - Laurentia Natalia Fortuna; Suprihatimi SW; Dorothea Ririn Indriastuti (PENG: Jurnal Ekonomi dan Manajemen, 2026)
Financial management is the activity of planning, organizing, staffing, implementing, and controlling financial functions. The main goal of financial management is to maximize the value of the company. One of the indicators used to measure company value in the capital market is stock price, as financial decisions are reflected in it. This study aims to analyze: 1) The influence Return on Assets on stock prices in property and real estate companies listed on the Indonesia Stock Exchange during the 2019–2023 period, 2) The influence of Earnings per Share on stock prices in property and real estate companies listed on the Indonesia Stock Exchange during the 2019–2023 period, 3) The influence of the Debt to Equity Ratio on stock prices in property and real estate companies listed on the Indonesia Stock Exchange during the 2019–2023 period.  The research method used is a quantitative method, utilizing SPSS 25.0 to analyze the data. The data source used in this study is secondary data. The population in this research consists of property and real estate companies listed on the Indonesia Stock Exchange. The sample consists of 17 companies, selected using a purposive sampling technique. The data collection method employed is literature study. The data analysis techniques include descriptive analysis, multiple linear regression analysis, t-test, F-test, and the coefficient of determination test. The results of the multiple linear regression analysis in this study are : Y = 4581.417 – 19963.401 X1 + 3686.066 X2 – 1623.543 X3 + e. The results of the t-test show that Return on Assets does not have a significant effect on stock prices of property and real estate companies listed on the Indonesia Stock Exchange; Earnings per Share has a significant effect on stock prices of property and real estate companies listed on the Indonesia Stock Exchange; and the Debt to Equity Ratio does not have a significant effect on stock prices of property and real estate companies listed on the Indonesia Stock Exchange. The results of the F-test show an F value of 10.940 with a significance value (p-value) of 0.001, which is less than 0.05. Therefore, H₀ is rejected and Hₐ is accepted, indicating that the model used in the study is appropriate for predicting the influence of the independent variables X1 (Return on Assets), X2 (Earnings per Share), and X3 (Debt to Equity Ratio) on the dependent variable, which is stock price (Y). The result of the coefficient of determination (adjusted R Square) for this model is 0.651, meaning that 65.1% of the variation in stock prices (Y) can be explained by the independent variables X1 (Return on Assets), X2 (Earnings per Share), and X3 (Debt to Equity Ratio). The remaining 34.9% is influenced by other variables outside the model.